Allometric equations for yield predictions of enset (Ensete ventricosum) and khat (Catha edulis) grown in home gardens of southern Ethiopia. (18th April 2017) - Mellisse, B.T.; Descheemaeker, K.; Mourik, M.J.; van de Ven, G.W.J.
Abstract: Enset is a large, single‐stemmed perennial herbaceous plant domesticated as a staple food crop only in Ethiopia. Khat is a perennial plant cultivated for its economically important leaves and twigs that are the sources of stimulant when chewed. We address the issue of yield estimation of both crops, as they are important for the livelihoods of smallholders in the home garden systems in Southern Ethiopia and have received little attention so far. The objective of this study was to develop linear allometric models for estimating the edible (food and feed) and commercial yields of enset and khat plants, respectively. Data were collected from 20 enset and 100 khat plants. Diameter at 50‐cm height ( d 50 ), pseudostem height ( hp ) and their combination were good predictor variables for the food products of enset with adjusted R 2 values above 0.85, while d 50, h p, edible pseudostem height ( hep ), total height ( ht ) and their combination were good predictor variables for the feed products of enset with adjusted R 2 values above 0.70. For dwarf khat plants crown area ( ca ) combined with total height ( ht ) resulted in the best prediction with an adjusted R 2 of 0.77, while the leaf and twig dry weight for tall khat plants was best predicted by ca with adjusted R 2 of 0.43. In all cases linear models were used.